Prevalence of Dental Caries, Oral Hygiene Knowledge, Status, and Practices among Visually Impaired Individuals in Chennai, Tamil Nadu - James Rufus John; Breena Daniel; Dakshaini Paneerselvam; Ganesh Rajendran (International Journal of Dentistry)
Aim. To assess the prevalence of dental caries, oral hygiene knowledge, status, and practices among visually impaired individuals in Chennai, Tamil Nadu. Materials and Methods. A cross-sectional study was conducted among 404 visually impaired individuals in Chennai city, Tamil Nadu. Four schools were randomly selected for conducting the study. The oral hygiene status, prevalence of caries, and knowledge and attitude towards oral care among visually impaired individuals were collected and analysed. Results. In the present study, whilst 42% of individuals had fair oral hygiene status, 33% had good hygiene followed by 25% having poor oral hygiene. The overall mean number of DMFT was estimated to be 4.5±2.7. The mean number of decayed teeth was 3.1±2.2, mean number of missing teeth was 0.8±1.4, and mean number of filled teeth was 0.5±1.3. Conclusion. Whilst oral hygiene status was found to be relatively fair, there was a high rate of dental caries among the sample population. This shows that there is lack of knowledge regarding oral health maintenance. Therefore, early identification of caries coupled with effective oral health promotion programs providing practical knowledge to visually impaired students would prove beneficial.